Sustainability of business in the context of environmental management - Pritwani, Kamlesh (CRC PRESS, 2018)
Sustainability of Business in the Context of Environmental Management studies the newly emerged concept of 'sustainable business' in view of the growing Indian economy. It explores the current corporate social responsibility practices adopted with special reference to environmental management in Indian companies.The book compares the legal, financial, economic, industrial, and social behavioural aspects. Out of these aspects, industrial aspect in view of 'environmental management' is discussed in detail. It also explores the forces driving the changing relationship between business and society and corporate leadership reacting to environmental challenges. Finally, the book restates the concept of increasing profitability through societal development. Please note: This volume is Co-published with The Energy and Resources Institute Press, New Delhi. Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka